Informasi dan promosi kesehatan rumah sakit dalam meningkatkan kesehatan masyarakat - Anisa, Renata; Dewi, Retasari; Yustikasari, Yustikasari (Faculty of Communication, Padjadjaran University, 2025)
Health promotion in hospitals is implemented based on the Regulation of the Minister of Health No. 44 of 2018 concerning the Implementation of Hospital Health Promotion. Health promotion is a community empowerment process that provides information, influences, and assists communities in supporting behavioral and environmental changes. Hospitals, both public and private, are required to conduct health promotion following the principles of a healthy paradigm to improve public health. This qualitative descriptive study aims to determine the types of information, health promotion tactics, and communication media used by the Regional General Hospital (RSUD) in Subang Regency. Data collection techniques employed library studies, observations, and in-depth interviews with the hospital's health promotion team. The results showed that health promotion in hospitals has been carried out since 2015. Information and health promotion programs include health counseling at the hospital, community outreach, community education, and health talk shows. The information conveyed consists of hospital services, diseases and treatment, and health tips. Communication media used include audio media in the hospital, print media (leaflets, brochures, and billboards), and digital media (websites, Facebook, Instagram, and YouTube) to reach a wider audience.